Experimental study on the effect of different cement content on the improvement of dynamic characteristics of seismic-prone poor soil - Zhao, Yunhui; Qiao, Feng; Meng, Fanchao; Zheng, Zhihua; Gu, Jiapei; Li, Haoyu (PloS one, 2024)
The improvement of sandy soils with poor seismic properties to modify their dynamic characteristics is of great importance in seismic design for engineering sites. In this study, a series of dynamic tests on sandy soils sandy soils with poor seismic conditions were conducted using the GCTS resonant column system to investigate the improvements effects of different cement contents on dynamic characteristic parameters. The research findings are as follows: The cement content has certain influences on the dynamic shear modulus, dynamic shear modulus ratio, the maximum dynamic shear modulus, and the damping ratio of sandy soils with poor seismic properties. Among them, the influence on dynamic shear modulus is limited, while the damping ratio is significantly affected. The addition of cement to seismic-poor sandy soils significantly enhances their dynamic characteristics. The most noticeable improvement is observed when the cement content is 8%. Through curve fitting analysis, a relationship equation is established between the maximum dynamic shear modulus and the cement content, and the relevant parameters are provided. A comparative test between the improved soils and the remolded soils reveals that the addition of cement significantly improves the seismic performance of the poor soils. The recommended values for the range of variation of the dynamic shear modulus ratio and damping ratio are provided, considering the effect of improvement. These research findings provide reference guidelines for seismic design and engineering sites.